Right ventricular-pulmonary artery coupling in tricuspid regurgitation: prognostic value and impact of treatment strategy - Rommel, Karl-Philipp; Schlotter, Florian; Stolz, Lukas; Kresoja, Karl-Patrik; Kassar, Mohammad; Praz, Fabien; Estevez-Loureiro, Rodrigo; Maisano, Francesco; Van Belle, Eric; Bonnet, Guillaume; Kalbacher, Daniel; Ludwig, Sebastian; et al. (JACC Cardiovascular interventions, 2025)
Background - Right ventricular-pulmonary artery coupling (RVPAC) predicts outcomes after transcatheter tricuspid valve edge-to-edge repair (T-TEER), but its role in patient selection remains unclear. - Objectives - The aim of this study was to evaluate the prognostic implications of RVPAC in a European registry of patients with tricuspid regurgitation undergoing either T-TEER or medical management. - Methods - Among 1,885 patients with tricuspid regurgitation (n = 585 medical, n = 1,300 T-TEER), 946 were propensity matched (1:1). RVPAC, assessed as the ratio of tricuspid annular plane systolic excursion to systolic pulmonary artery pressure was analyzed for its association with 1-year mortality. - Results - RVPAC was significantly associated with mortality (HR: 0.11; 95% CI: 0.04-0.29; P < 0.01), with an optimized cutoff of 0.41 mm/mm Hg. Mortality differed significantly by RVPAC in both treatment groups (log-rank P < 0.01). Across RVPAC tertiles (<0.32, 0.32-0.46, and >0.46 mm/mm Hg), tricuspid annular plane systolic excursion increased (14 mm [Q1-Q3: 12-17 mm] vs 18 mm [Q1-Q3: 15-20 mm] vs 21 mm [Q1-Q3: 18-24 mm]; P < 0.01), while systolic pulmonary artery pressure (60 mm Hg [Q1-Q3: 50-70 mm Hg] vs 45 mm Hg [Q1-Q3: 40-52 mm Hg] vs 34 mm Hg [Q1-Q3: 29-41 mm Hg]; P = 0.30) and kidney function (43 mL/min/m2 [Q1-Q3: 30-57 mL/min/m2] vs 49 mL/min/m2 [Q1-Q3: 38-67 mL/min/m2] vs 53 mL/min/m2 [Q1-Q3: 40-69 mL/min/m2]; P = 0.03) declined. Mortality was highest in the low RVPAC tertile, with no difference between treatment modalities (HR: 1.04; 95% CI: 0.68-1.61; P = 0.85). T-TEER was associated with better survival than medical management in the intermediate RVPAC tertile (HR: 0.54; 95% CI: 0.31-0.94; P = 0.03). This difference persisted but weakened in the high RVPAC tertile, with the overall most favorable outcomes (HR: 0.69; 95% CI: 0.35-1.36; P = 0.27). - Conclusions - Poorer RVPAC reflects higher baseline risk and mortality, regardless of treatment. T-TEER is associated with better survival across a range of RVPAC values, including those less than previously suggested thresholds.
Online verfügbar: 9. Juni 2025
Gesehen am 29.10.2025